Bridging the Gap: The Value of Science in Coaching - Andrew Langford (International Universities Strength and Conditioning Association, 2020)
Science is one of the greatest achievements of mankind. It has saved billions of lives, created astonishing technology, solved global problems, and helped raise the standard of living for all. But science is often misinterpreted and misapplied, and sometimes has a negative reputation in the coaching community. Part of the problem is that the definition of science varies for different people. We may use the word science to mean the facts that we know about the world - the force of gravity, the mass of an object, the anatomy of the knee etc. These are clear, objective facts, and cannot be disputed. However, we may also use the term science to mean scientific thinking, clear thinking, or critical thinking. This is where we might not know the exact facts about something, but we can use the principles of evidence, logic, rationality and reason to make a strong inference about it. We can then test, analyse and evaluate, deciding on what has worked and why. This is evidence-based practice.  Scientist Carl Sagan put it well when he said, "science is a way of thinking much more than it is a body of knowledge."